Climate Variability and Its Effects on Rice (Oryza sativa L.) Productivity, Pest Incidence, and Disease Occurrence in Pematang Setrak Village, Teluk Mengkudu District, Serdang Bedagai Regency, Indonesia - Nurhayati Nurhayati; Aranda Muttaqi Hasibuan; Murni Sari Rahayu (Jurnal Penelitian Pendidikan IPA, 2025)
This study employed a survey method with field data collection to analyze the relationship between rainfall and rainy days on irrigated rice productivity. The analysis was conducted using correlation tests to determine the strength of the relationship between variables, as well as multiple linear regression to examine the influence of climatic variables on productivity. The results indicate that rainfall and rainy days do not have a significant relationship with productivity. This is because the irrigated rice cultivation system is supported by adequate irrigation, so it does not entirely depend on rainfall conditions. Based on interview results, the average farmer owns approximately 1 hectare of land with productivity reaching 7–8 tons/ha using the varieties Inpari 32, Ciherang, and Mekongga. Regression analysis results indicate that rainfall and rainy days together account for 60.57% of the variation in productivity, while 40.43% is influenced by other factors such as fertilization, variety, and crop maintenance. Additionally, an analysis of pests and diseases revealed that some pests showed no significant correlation with climatic variables, while diseases such as blast and leaf spot exhibited a significant relationship with rainfall and rainy days